Electrolyzed water as a disinfectant: A systematic review of factors affecting the production and efficiency of hypochlorous acid. (October 2021) - Ampiaw, Rita E.; Yaqub, Muhammad; Lee, Wontae
Abstract: Currently, electrolyzed water, a sustainable and environmentally friendly disinfectant produced through electrolysis of an acid or salt, has become very popular because of its applications in various sectors such as health, agriculture, and food. Influencing factors are important for optimizing the electrolyzed water production process and maximizing application efficiency. Factors that influence the production and efficiency of electrolyzed water, including water and electrolyte properties, electrode material, current, storage, and application factors, were reviewed in this study. Moreover, some commercially available generator models, their specifications, and issues are discussed along with future recommendations. This work summarizes the available literature from January 2000 to December 2020, reporting studies that can assist in understanding various parameters affecting the production and stability of electrolyzed water. This can provide further insights and aid researchers in optimizing the process and address the issues faced by the existing systems by offering new perspectives in future studies. Graphical abstract: Unlabelled Image Highlights: Reviewed production routes of electrolyzed water (EW) Studied influencing parameters in EW production process Discussed optimum parameters presented in the literature Explored the existing commercial generators and emerging issues Suggested future recommendations to improve the production and efficiency of EW